KNOWLEDGE TO INCREASE NURSING WORK PERFORMANCE INPATIENT CARE: EMPIRICAL STUDY AT RSUD TAMANSARI - Mochammad Adam Eldi; Supriyantoro Supriyantoro; Arrozi Adhikara (Jurnal Health Sains, 2023)
The hospital has the role of providing a holistic health care services. Nursing personnel makes up the largest proportion, which are almost 50% of all hospital human resources. The purpose of this study is to determine the effect analysis of motivation, workload and knowledge on the performance of nursing staff at RSUD Tamansari inpatient care. The method used in this study is cross sectional in the form of quantitative causality. Data collection used a survey method by taking questionnaires from 41 nurses in the inpatient unit of RSUD Tamansari. The sampling technique used in this study is total sampling. The analysis between variables using multiple linear regression test. The results showed that motivation and knowledge variables had a significant value of <0.05, while the workload variable had a significant value of >0.05. The research findings show that the dominant knowledge variable influences the performance of nursing staff inpatient care at RSUD Tamansari. The conclusion in this study is that motivation and knowledge have a direct and significant effect on the performance of nursing staff at inpatient care at RSUD Tamansari and workload does not have a direct and significant effect on the performance of nursing staff at inpatient care at RSUD Tamansari. One of the managerial implications is that hospital management and training units need to improve the education and training system as a priority.